A Historical Analysis of Media Practices and Technologies in Protest Movements: A Review of Crisis and Critique by Anne Kaun - Laajalahti, Anne (2017)
Dr. Anne Kaun’s book, Crisis and Critique: A Brief History of Media Participation in Times of Crisis (London: Zed Books, 2016, 131 pp., ISBN: 978-1-78360-736-5), is a concise but comprehensive analysis of the changing media practices and technologies in protest movements. The book overviews the topic within the context of major economic crises and scrutinises three richly detailed case studies in the United States: (a) the unemployed workers’ movement during the Great Depression in the 1930s, (b) the tenants’ rent strike movement of the early 1970s, and (c) the Occupy Wall Street movement following the Great Recession of 2008. Kaun begins her book with an introduction to economic crises and protest movements and highlights the relationship of crisis and critique to media practices. She goes on to investigate historical forms of media participation in protest movements from three different perspectives: (a) protest time, (b) protest space, and (c) protest speed. The book contributes to the recent discussion on the emerging role of social media in protest by providing a historically nuanced analysis of the media participation in times of crisis. As a whole, the book is valuable to anyone interested in media and social activism.